Rally caps [videorecording (DVD)] - Cutler, Stephen J.; Smart, Amy, 1976-; Hirsch, Judd; Minniear, Carson; Kluge, Kim Allen, 1959-; Kluge, Kathryn, 1974- (BMG Global, 2024)
RALLY CAPS is a heartwarming tale of friendship. A young boy, Jordy, is seriously injured during a Little League baseball tryout. At a summer camp, he bonds with a deaf boy, Lucas, who recently had Cochlear Implant surgery. Their friendship becomes the driving force as the pitcher/catcher duo leads their team in the camp championship game.